1999
DOI: 10.1136/bjo.83.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diode laser trans-scleral cyclophotocoagulation in the management of glaucoma after intravitreal silicone oil injection for complicated retinal detachments

Abstract: Aims-To evaluate the eVect of trans scleral cyclophotocoagulation (TSCPC) on intraocular pressure (IOP) in the eyes retaining intravitreal silicone oil with medically uncontrolled secondary glaucoma following intravitreal silicone oil injection. Methods-Medical records of 11 eyes of 11 patients who underwent TSCPC for medically uncontrolled glaucoma without pupillary block following intravitreal silicone oil injection for complicated retinal detachment were reviewed retrospectively. In all cases, intravitreal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 17 publications
2
31
0
2
Order By: Relevance
“…Trans-scleral cyclodiode photocoagulation (TSCPC) has been demonstrated as a safe and effective method of treating intractable glaucoma in eyes retaining silicone oil. [1][2][3] Below, we describe the effect on IOP of TSCPC based on the retrospective review of medical records of patients with intravitreal silicone oil and intractable glaucoma.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Trans-scleral cyclodiode photocoagulation (TSCPC) has been demonstrated as a safe and effective method of treating intractable glaucoma in eyes retaining silicone oil. [1][2][3] Below, we describe the effect on IOP of TSCPC based on the retrospective review of medical records of patients with intravitreal silicone oil and intractable glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nguyen et al 6 reported a higher incidence of 48%. 5 The glaucoma associated with intravitreal silicone oil presents a difficult management problem.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However one case underwent a modified Schocket procedure but didn't achieve normal IOPs. Transscleral cyclophotocoagulation has shown successful IOP control in 74-82% of patients after 1 year although the visual function was poor in these patients (Bloom et al 1997 andHan et al, 1999). Early removal of silicone oil (6/12) has been noted to have reduced risk of secondary glaucoma and similar redetachment rates (Han et al 1998).…”
Section: Management Optionsmentioning
confidence: 99%